Is Toxoplasma Gondii Infection Related to Brain and Behavior Impairments in Humans? Evidence from a Population-Representative Birth Cohort. - Karen Sugden; Terrie E Moffitt; Lauriane Pinto; Richie Poulton; Benjamin S Williams; Avshalom Caspi (PLoS ONE)
Background Toxoplasma gondii (T. gondii) is a protozoan parasite present in around a third of the human population. Infected individuals are commonly asymptomatic, though recent reports have suggested that infection might influence aspects of the host's behavior. In particular, Toxoplasma infection has been linked to schizophrenia, suicide attempt, differences in aspects of personality and poorer neurocognitive performance. However, these studies are often conducted in clinical samples or convenience samples. Methods/results In a population-representative birth-cohort of individuals tested for presence of antibodies to T. gondii (N = 837) we investigated the association between infection and four facets of human behavior: neuropsychiatric disorder (schizophrenia and major depression), poor impulse control (suicidal behavior and criminality), personality, and neurocognitive performance. Suicide attempt was marginally more frequent among individuals with T. gondii seropositivity (p = .06). Seropositive individuals also performed worse on one out of 14 measures of neuropsychological function. Conclusion On the whole, there was little evidence that T. gondii was related to increased risk of psychiatric disorder, poor impulse control, personality aberrations or neurocognitive impairment.